2013
DOI: 10.3390/insects4040631
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogenic Fungi Associated with Exotic Invasive Insect Pests in Northeastern Forests of the USA

Abstract: Mycopathogens of economically important exotic invasive insects in forests of northeastern USA have been the subject of research at the Entomology Research Laboratory, University of Vermont, for the last 20 years. Elongate hemlock scale, European fruit lecanium, hemlock woolly adelgid and pear thrips were analyzed for the presence of mycopathogens, in order to consider the potential for managing these pests with biological control. Fungal cultures isolated from insects with signs of fungal infection were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The present findings were in accordance with Gouli et al, (2013) who also isolated EPF such as Aspergillus, Fusarium and Penicillum. In present investigation, 5.22% of EPF Metarhizium sp.…”
Section: Rhizopussupporting
confidence: 93%
“…The present findings were in accordance with Gouli et al, (2013) who also isolated EPF such as Aspergillus, Fusarium and Penicillum. In present investigation, 5.22% of EPF Metarhizium sp.…”
Section: Rhizopussupporting
confidence: 93%
“…Cultures were identified microscopically using light microscope (OLYMPUS CX41, Olympus Corporation, Tokyo, Japan) after the fungi were fixed with the scotch tape imprint method [ 25 ] and stained with lactophenol cotton blue. Platinum coating on the surface of the microfungi was done by using JEOL auto fine coater (JFC-1600, JEOL Ltd., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Lomer et al indicated that entomopathogenic fungi biopesticide kills 70 -90% of treated locusts within 14-20 days [51]. The mortality of the brown marmorated stink bug after 12 -28 days ranged from 67 to 100% and 40 to 88% by Beauveria and Metarhizium isolates, respectively [52,47,53].…”
Section: Discussionmentioning
confidence: 99%